Genetic biomarkers of posttraumatic epilepsy: A systematic review. (March 2017) - Cotter, Devyn; Kelso, Andrew; Neligan, Aidan
Highlights: The field of epilepsy biomarkers remains is in its infancy. All the potential biomarkers discussed are preliminary work requiring validation. The most promising genetic biomarkers are IL-1β rs1143634 and A1AR rs10920573. Abstract: Introduction: Posttraumatic epilepsy (PTE) is caused by traumatic brain injury (TBI) and is an important contributor to the overall social and economic burden of epilepsy. Epidemiological studies suggest that there is a genetic contribution to the development of PTE. Identification of clinically useful genetic biomarkers is important for advancements in diagnosis and treatment of PTE. Methods: A systematic review was performed on the existing literature of genetic biomarkers of posttraumatic epilepsy (PTE). A multi-database search yielded 4 articles deemed suitable for review. Potential genetic biomarkers were identified and critically evaluated. Results & discussion: Biomarkers identified included single nucleotide polymorphism (SNP) rs1143634 of the interkeukin-1β (IL-1β) gene, SNPs rs3828275, rs3791878, and rs769391 of the glutamic acid decarboxylase 1 (GAD1) gene, SNPs rs3766553 and rs10920573 of the adenosine A1 receptor (A1AR) gene, and the functional variant C677T of the methylenetetrahydrofolate reductase (MTHFR) enzyme. The most promising biomarkers identified were IL-1β rs1143634 and A1AR rs10920573. Both had heterogenous at risk genotypes (CT). Those with IL-1β rs1143634 CT genotype developed PTE in 47.7% of cases (p = 0.008) and those with A1AR rs10920573 CT genotype developed PTE in 19.2% of cases (p = 0.022). Conclusion: The majority of articles were preliminary with a need for validation of results. There is a need for continued high calibre research in order to validate the currently identified genetic biomarkers as well as to discover new genetic biomarkers in PTE.